2019
DOI: 10.3390/v11111007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Influenza A Virus A/WSN/1933 (H1N1) Infected A549 Cells during First Cycle of Viral Replication

Abstract: Influenza A virus (IAV) has developed strategies to utilize host metabolites which, after identification and isolation, can be used to discover the value of immunometabolism. During this study, to mimic the metabolic processes of influenza virus infection in human cells, we infect A549 cells with H1N1 (WSN) influenza virus and explore the metabolites with altered levels during the first cycle of influenza virus infection using ultra-high-pressure liquid chromatography–quadrupole time-of-flight mass spectromete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 60 publications
4
39
0
Order By: Relevance
“…Unfortunately, in this time frame, A549 metabolism is influenced by cell cycle and replication, potentially confounding this study 65 . Nonetheless, within 8 hours, IAV altered the A549 TCA cycle (ie, decreased acetyl‐CoA and increased glutamic acid) 66 . Moreover, transcriptomic analysis of chicken lung epithelial cells infected with a low pathogenic H6N2 strain showed avian influenza virus increased OXPHOS 67 .…”
Section: Influenza Metabolic Reprogrammingmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, in this time frame, A549 metabolism is influenced by cell cycle and replication, potentially confounding this study 65 . Nonetheless, within 8 hours, IAV altered the A549 TCA cycle (ie, decreased acetyl‐CoA and increased glutamic acid) 66 . Moreover, transcriptomic analysis of chicken lung epithelial cells infected with a low pathogenic H6N2 strain showed avian influenza virus increased OXPHOS 67 .…”
Section: Influenza Metabolic Reprogrammingmentioning
confidence: 98%
“…65 Nonetheless, within 8 hours, IAV altered the A549 TCA cycle (ie, decreased acetyl-CoA and increased glutamic acid). 66 Moreover, transcriptomic analysis of chicken lung epithelial cells infected with a low pathogenic H6N2 strain showed avian influenza virus increased OXPHOS. 67 Induction of energy metabolism proteins, such as ATP synthase and cytochrome b5 type A in the mitochondria, occurs during IAV infection of A549, and inhibition of OXPHOS reduces IAV replication without apparent cellular toxicity.…”
Section: In Vitro Studies Of Iav Metabolismmentioning
confidence: 99%
“…Analysis of differential expressed circRNAs has revealed changes in the metabolism of fatty acids upon BmCPV infection ( Hu et al, 2018 ).All these reports have demonstrated that lipid-related metabolisms play vital roles in the life cycles of RNA viruses. It is worth noting that the virus-induced changes of cellular metabolic activity generally facilitate the progress of virus infection ( Diop et al, 2018 ; Tian et al, 2019 ). To date, the lipid metabolism in cells infected by double-stranded RNA (dsRNA) viruses, such as, BmCPV remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan metabolites serotonin and kynurenin are differently enriched in patients with dengue hemorrhagic fever (DHF) suggesting that these metabolites can be used in combination with IFN-γ as accurate metrics for early prognosis of DHF [51]. Analysis of Influenza A virus-infected cells reveals alterations in several metabolites of the purine, lipid and glutathione pathways, resulting in acceleration of viral replication [20].…”
Section: Immunometabolismmentioning
confidence: 99%
“…Of note, a large portion of the metabolome includes relatively underexamined lipid families [15]. There are thus still uncharted areas of the metabolome that may be key to the host response to infection [16][17][18][19][20] and vaccines [21].…”
Section: Introductionmentioning
confidence: 99%